Strategi Ekslusi Pada Berita Online Detikjabar.Com “Jejak Berdarah Pembantaian di Pangandaran Tahun 1999” Kajian Analisis Wacana Kritis Perspektif Theo Van Leeuwen - Andini, Ayu Sri; Hamdani, Agus (Fakultas Ilmu Budaya, Universitas Jambi, 2024)
The use of critical theory as an analytical tool in research aims to describe the exclusion strategies in the crime news titled